PERAN PEMBIAYAAN AKAD QARDHUL HASAN TERHADAP KESEJAHTERAAN PEDAGANG (STUDI KASUS: PENERIMA PROGRAM PINJAMAN BEBAS RIBA YAYASAN ROMBONG SEDEKAH) - Wahyu Tri Wulandari; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study examines the role of qardhul hasan contract financing through a free loan program on Rombong Sedekah Foundation Jombang whether to improve the prosperity of super micro traders. The qardhul hasan contract is a contract whereby the borrower is not required to pay anything but the loan capital, but the borrower is allowed to give a portion of the profits to the lender in the form of a gift or grant but on one condition there is no agreement in advance. This research is a descriptive qualitative research by interviewing 10 informants. This study shows that the qardhul hasan contract on the riba free loan program has an impact in improving the welfare of the traders, and based on the indicators of maqashid shariah the traders have felt the impact of changes in their lives, that is to worship 5 days of worship, to receive proper education, responsible to their offspring , fulfilling the needs of the inner and outer by following the study conducted by the foundation, and experiencing an increase in income since following the free loan program, in addition they also no longer borrow to loanen borrowers or racially.Keywords: Qardhul Hasan, foundation, welfare, and Maqashid ShariahREFFERENCESBadan Pusat Statistik. 2017. Jumlah Penduduk Miskin di Indonesia Periode Maret 2015-Maret 2017 (Dalam Jiwa). Retrieved from www.bps.go.idPratama, Y. C. 2014. Analisis Faktor-Faktor yang Mempengaruhi Kemiskinan Di Indonesia. Esensi: Jurnal Bisnis dan Manajemen, 4(2).Kara, M. 2012. Pemikiran Al-Syatibi tentang Maslahah dan Implementasinya dalam Pengembangan Ekonomi Syariah. Jurnal Assets, 2(2), 173-184.Widodo, H., & Kustiawan, T. 2001. Akuntansi& Manajemen Keuangan        Untuk       Organisasi PengelolaZakat:Institut Manajemen Zakat.Umam, K., & Utomo, S. B. 2016. Perbankan Syariah: Dasar-Dasar dan Dinamika Perkembangannya Di Indonesia. Jakarta: PT Raja Grafindo Persada.Pusparini, M. D. 2015. Konsep Kesejahteraan Dalam Ekonomi Islam (Perspektif Maqasid Asy- Syari’ah). Islamic Economics Journal, 1(1), 45-59.